Dispersion coefficient for unsteady salinity intrusion in estuaries - Luong Thi Duy Hieu; Suphat Vongvisessomjai; Gupta, Ashim Das; Tanaka, Hitoshi; Sutat Weesakul; The Government of Denmark (Bangkok : Asian Institute of Technology, 1993)
In the past dispersion coefficient in the Mekong estuarine system has been firstly assumed to be constant and later on expressed as a function of existing salinity and its gradient along the estuary. In this study some hydrodynamic characteristics are investigated and found to be additional factors describingdispersion coefficient. In the otherword, the salinity gradientplays the mostimportant role in the mixing process between sea and river water; it has the main effect on the behavior of the dispersion coefficient. Turbulence which characterized by velocity is also involved in the dispersion process. Itis found from this study thatdispersion coefficientin Mekongestuarine system can beexpressed as a function in space and in time of parameters such as: salinity concentration, salinity concentration gradient, hydraulic radius, flow velocity. From the computational results, the variation of dispersion coefficient along every branch in the Mekong estuarine system is also specified. That is a very convenienttool forthe estimation ofdispersioncoefficientwhen solving the Advective-Dispersion equation to predict the salinity intrusion in the Mekong estuarine system.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfillment ofthe requirements for the Degree ofMaster of Engineering.
Keywords: Saltwater encroachment